Visual pathway abnormalities were found in most multiple sclerosis patients despite history of previous optic neuritis - Stella Maris Costa Castro; Alfredo Damasceno; Benito Pereira Damasceno; Jose Paulo de Vasconcellos; Fabiano Reis; Josie Naomi Iyeyasu; Keila Monteiro de Carvalho (Arquivos de Neuro-Psiquiatria)
Objective It was to investigate visual field (VF) abnormalities in a group of multiple sclerosis (MS) patients in the remission phase and the presence of magnetic resonance imaging (MRI) lesions in the optic radiations. Methods VF was assessed in 60 participants (age range 20-51 years): 35 relapsing-remitting MS patients [20 optic neuritis (+), 15 optic neuritis (-)] and 25 controls. MRI (3-Tesla) was obtained in all patients. Results Visual parameters were abnormal in MS patients as compared to controls. The majority of VF defects were diffuse. All patients except one had posterior visual pathways lesions. No significant difference in lesion number, length and distribution was noted between patients with and without history of optic neuritis. One patient presented homonymous hemianopsia. Conclusion Posterior visual pathway abnormalities were found in most MS patients despite history of previous optic neuritis.